2020
DOI: 10.5223/pghn.2020.23.4.366
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and the Development of Functional Gastrointestinal Disorders in Infants

Abstract: Purpose To assess the association between birth weight and the development of functional gastrointestinal disorders (FGIDs) in the first year of life. Methods This is a secondary analysis of a prospective cohort multicenter study including neonates, consecutively enrolled at birth, and followed up for one year. At birth all infants were classified by birth weight as extremely low (ELBW), very low, or low when <1,000, <1,500, and <2,500 g, respectively, and by birth weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…We also found that infants with a gestational age of fewer than 32 weeks have an enhanced risk of infantile colic and infant regurgitation. As reported in Danish and Italian studies, infants with lower birth weights are at double risk (or even higher) for developing infantile colic [24,25] . In line with this, our results indicated that low birth weight (<1.5 kg) has been linked to an elevated risk of infantile colic as well as regurgitation.…”
Section: Discussionmentioning
confidence: 70%
“…We also found that infants with a gestational age of fewer than 32 weeks have an enhanced risk of infantile colic and infant regurgitation. As reported in Danish and Italian studies, infants with lower birth weights are at double risk (or even higher) for developing infantile colic [24,25] . In line with this, our results indicated that low birth weight (<1.5 kg) has been linked to an elevated risk of infantile colic as well as regurgitation.…”
Section: Discussionmentioning
confidence: 70%
“…This finding was opposed by a study from Aryastami et al (2017), which showed a strong significant relationship between low birth weight and the incidence of stunting with (p<0.001). Children with low birth weight tend to have functional gastrointestinal disorders (Baldassarre et al, 2020). Also, food intolerance often happens in children with very low birth weight or low birth weight who are premature (Carter, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Infantile colic represents a self-limited condition, but continues to remain a major cause of concern for parents and of distress for infants ( 27 ). Recently, a large Italian prospective study recruiting infants since birth and monitoring up to 1 year of life, showed a high incidence of colic (50.7%) particularly expressed in infants born preterm, with low birth weight or exposed to antibiotics in the perinatal period ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%